2007
DOI: 10.2967/jnumed.106.037291
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET Scanning Correlates with Tissue Markers of Poor Prognosis and Predicts Mortality for Patients After Liver Resection for Colorectal Metastases

Abstract: 18 F-FDG PET has proven invaluable in the staging of patients with metastatic colorectal cancer. The aim of the current study was to determine whether this biologic scan would correlate with other cellular characteristics and the clinical behavior of tumors. Methods: Ninety patients with resectable colorectal cancer metastatic to the liver underwent 18 F-FDG PET before hepatectomy. At surgery, tumors were harvested and prepared for assessment by histology and immunohistochemistry. Expression of Ki67 (a marker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
66
2
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 16 publications
4
66
2
4
Order By: Relevance
“…Although we included only patients treated with thermal ablation therapy, our results are consistent with findings by other authors [8,[22][23][24]. A recent meta-analysis pooled the data on the prognostic significance of metabolic parameters and patients' survival and found a significant association between a high pretreatment SUV and a poor OS (pooled hazard ratio of 1.24, 95% CI 1.06-1.45) [26].…”
Section: Modelsupporting
confidence: 79%
See 1 more Smart Citation
“…Although we included only patients treated with thermal ablation therapy, our results are consistent with findings by other authors [8,[22][23][24]. A recent meta-analysis pooled the data on the prognostic significance of metabolic parameters and patients' survival and found a significant association between a high pretreatment SUV and a poor OS (pooled hazard ratio of 1.24, 95% CI 1.06-1.45) [26].…”
Section: Modelsupporting
confidence: 79%
“…Previous studies reported the prognostic significance of metabolic parameters for the survival of patients with surgically treated CLM [8,[22][23][24]. However, to our knowledge, this is the first study that investigated this for patients with CLM treated by means of curativeintent thermal ablation with stratified results for site of recurrence.…”
Section: Modelmentioning
confidence: 75%
“…A study by De Geus-Oei et al reported that a high SUV of hepatic metastases is significantly associated with poor survival, although the study included both patients who underwent surgery and patients who received chemotherapy (15). Riedl et al demonstrated that the SUV max of hepatic metastases is associated with tissue markers of poor prognosis (glucose transporter 1, Ki-67, and p53) and prognosis itself, but there was no mention of whether the liver metastases were synchronous or metachronous and whether the SUV max was for the primary tumor or the hepatic metastasis (16). Recently, Muralidharan et al have reported that the MTV and TLG, but not SUV max , of a hepatic metastasis is significantly associated with prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET/CT uses the increased rates of glucose metabolism in tumors to characterize the biology of different cancers, with several studies having reported that high rates of 18 F-FDG uptake in tumors are associated with increased aggressiveness and poor survival (13,14). However, only a limited number of studies have addressed the prognostic ability of 18 F-FDG PET/CT in patients with CRC liver metastasis (15)(16)(17). In particular, no published article has dealt exclusively with SCLM, for which the prognosis is worse than the prognosis for metachronous metastasis.…”
mentioning
confidence: 99%
“…Several studies have shown that high glucose uptake or Glut-1 expression predicts poor prognosis and that Glut-1 levels often are elevated in 18F-FDG-avid tumors, [30][31][32][33][34][35][36][37][38][39][40][41] but their regional or microregional spatial association has seldom been studied and remains unclear. Our colocalization analysis of 18 F-FDG uptake and Glut-1 expression shows some, albeit weak, spatial linkage and again the strongest correlation was observed in the relatively nonglycolytic tumor model (Table I).…”
Section: Discussionmentioning
confidence: 99%